Differences of Fixed Lift Net Catch Result by Using CFL Lamps and Underwater LED in Banten Bay Water - M Johar Rudin; Ririn Irnawati; Ani Rahmawati (JURNAL PERIKANAN DAN KELAUTAN, 2017)
The utilization of lamps as fishing aids related with the behavior of fish who like light. The lamp who use in this research are Compact Fluorescent Lamp (CFL) and Light Emitting Diode (LED). The purposes is know the illumination of light on the water medium and the composition of the catch of the tap on the CFL and underwater LED. The research was conducted from March to June 2017, located in the Banten Bay Water which has direction of position 05057'873